Intersections of Harm : Narratives of Latina Deviance and Defiance - Halperin, Laura, 1974- (Book collections on Project MUSE., 2015)
"In this innovative new study, Laura Halperin examines literary representations of harm inflicted on Latinas' minds and bodies, and on the places Latinas inhabit, but she also explores how hope can be found amid so much harm. Analyzing contemporary memoirs and novels by Irene Vilar, Loida Maritza Perez, Ana Castillo, Cristina García, and Julia Alvarez, she argues that the individual harm experienced by Latinas needs to be understood in relation to the collective histories of aggression against their communities. Intersections of Harm is more than just a nuanced examination of the intersections among race, ethnicity, class, gender, and sexuality. It also explores the intersection between two representations of harm within Latina literature: as a symptom of individual deviance and as an act of communal defiance. Halperin proposes that, ironically, being labeled as a madwoman can be both a source of harm and a means for hope, as it fuels the Latina protagonists' ability to recognize, remember, and resist harm. In this analysis, Halperin broadens the parameters of literary studies of female madness, as she compels us to shift our understanding of where madness lies. She insists that the madness readily attributed to individual Latinas is entwined with the madness of institutional structures of oppression, and she maintains that psychological harm is bound together with physical and geopolitical harm. In her pan-Latina study, from the Caribbean to Mexico to the United States, Halperin shows how each writer's work emerges from a unique set of locales and histories, but she also traces a network of connections among them. Bringing together concepts from feminism, postcolonialism, illness studies, and ecocriticism, Intersections of Harm opens up exciting new avenues for Latina/o studies."--